2020
DOI: 10.1101/2020.01.27.921122
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Apaf-1 Pyroptosome Senses Mitochondrial Permeability Transition

Abstract: HighlightsBile acids trigger caspase-4/11 and GSDME dependent pyroptosis Caspase-4/11 is a general sensor of mitochondrial permeability transition (MPT) MPT drives Apaf-1/capase-4 pryoptosome assembly Caspase-11 and GSDME mediated pyroptosis underlies cholesteric liver damage eTOC Blurb Persistent mitochondrial permeability transition elicited by bile acids, calcium overload and specifically ANT1 activators drives assembly of Apaf-1-capase-4/11 pyroptosome triggering GSDME dependent pryroptosis. 3 SUMMARY Casp… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
1
1
0
Order By: Relevance
“…These data indicate that BID serves downstream of CASP2 to activate GSDME-mediated pyroptosis. As described above, tBID targets the mitochondria to promote depolarization and the intrinsic apoptosis cell death pathways (Bock & Tait, 2020;Xu et al, 2021). Accordingly, we observed that HSV-2 infection strongly impaired mitochondrial function as measured by NADPH reductase activity (Fig 4G).…”
Section: Casp2 Induces Bid Cleavage To Mediate Mitochondria-dependent...supporting
confidence: 66%
“…These data indicate that BID serves downstream of CASP2 to activate GSDME-mediated pyroptosis. As described above, tBID targets the mitochondria to promote depolarization and the intrinsic apoptosis cell death pathways (Bock & Tait, 2020;Xu et al, 2021). Accordingly, we observed that HSV-2 infection strongly impaired mitochondrial function as measured by NADPH reductase activity (Fig 4G).…”
Section: Casp2 Induces Bid Cleavage To Mediate Mitochondria-dependent...supporting
confidence: 66%
“…Cyto C also triggers the inositol trisphosphate (IP3) receptor, thereby increasing cytoplasmic Ca 2+ levels and ROS generation. Apaf-1 can also interact with caspase 4 to form a novel protein complex that further activates the caspase-3-GSDME signaling pathway, leading to rapid cell pyroptosis (Xu et al, 2021b). Activated caspases can also cleave GSDM proteins, releasing their N-terminal domains; the released domains bind to membrane lipids and continuously disrupt the inner and outer mitochondrial membranes while inducing cell pyroptosis (Liu et al, 2021;Miao et al, 2023).…”
Section: Mitochondrial Dynamics Imbalance and Reduced Membrane Integr...mentioning
confidence: 99%